The textual genesis of Wittgenstein's philosophical investigations - Venturinha, Nuno. (New York, NY : Routledge, 2013)
"Sixty years after its first edition, there is an increasing consensus among scholars that the work posthumously published as Philosophical Investigations represents something that is far from a complete picture of Wittgensteins second book project. G.H. von Wrights seminal research on the Nachlass was an important contribution in this direction, showing that the Wittgenstein papers can reveal much more than the source of specific remarks. This book specifically explores Wittgensteins Philosophical Investigations from the different angles of its originary conceptions, including the mathematical texts, shedding new light on fundamental issues in twentieth century and contemporary philosophy. Leading authorities in the field focus on newly published or hitherto unpublished sources for the interpretation of Wittgensteins later work and a Wittgenstein typescript, translated for the first time into English, is included as an appendix"--
part I. Argumentative uses -- part II. The significance of logic and mathematics.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Wittgenstein, Ludwig, -- 1889-1951.; Electronic books